Genetic associations for keratoconus: a systematic review and meta-analysis - Shi Song Rong (Nature Portfolio, 2017)
Abstract Genetic associations for keratoconus could be useful for understanding disease pathogenesis and discovering biomarkers for early detection of the disease. We conducted a systematic review and meta-analysis to summarize all reported genetic associations for the disease. We searched in the MEDLINE, Embase, Web of Science, and HuGENET databases for genetic studies of keratoconus published from 1950 to June 2016. The summary odds ratio and 95% confidence intervals of all polymorphisms were estimated using the random-effect model. Among 639 reports that were retrieved, 24 fulfilled required criteria as eligible studies for meta-analysis, involving a total of 53 polymorphisms in 28 genes/loci. Results of our meta-analysis lead to the prioritization of 8 single-nucleotide polymorphisms (SNPs) in 6 genes/loci for keratoconus in Whites. Of them 5 genes/loci were originally detected in genome-wide association studies, including FOXO1 (rs2721051, P = 5.6 × 10−11), RXRA-COL5A1 (rs1536482, P = 2.5 × 10−9), FNDC3B (rs4894535, P = 1.4 × 10−8), IMMP2L (rs757219, P = 6.1 × 10−7; rs214884, P = 2.3 × 10−5), and BANP-ZNF469 (rs9938149, P = 1.3 × 10−5). The gene COL4A4 (rs2229813, P = 1.3 × 10−12; rs2228557, P = 4.5 × 10−7) was identified in previous candidate gene studies. We also found SNPs in 10 genes/loci that had a summary P value < 0.05. Sensitivity analysis indicated that the results were robust. Replication studies and understanding the roles of these genes in keratoconus are warranted.